Views of the People of Kp. Babakan Ds. Banjarwaru Kec. Ciawi Regency Bogor on Vaccination and the Effect of Vaccination on the Economy - Utami, Rahayu Putri; Dali, Rahamat Mulyana (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2024)
At the end of 2019, the world was shocked by the emergence of a new type of coronavirus, namely Covid-19. The spread of the Covid-19 Virus has been increasing lately, especially through the emergence of the Covid-19 Delta variant, driving the spread of the pandemic significantly. Various government efforts in the world to control the spread of this virus encourage the development and distribution of Covid-19 vaccines to the community as an effort to control the flow of the spread of Covid-19, including in Indonesia. So that at the end of 2020, the government began importing vaccines from countries that have the latest vaccines for use in Indonesia. According to the Ministry of Health of the Republic of Indonesia, the government has been trying to import various types of vaccines from abroad such as Sinovac, Novavax, AstraZeneca, Pfizer, and Covax. These vaccines began to spread throughout Indonesia, including Bogor Regency also received 99,625 vials received by the Bogor Regency Government, consisting of Sinovac single dose 25,600 vials, Sinovac multidose 70,025 vials and Astazaneca 4,000 vials. However, the implementation of vaccination still has many obstacles due to the lack of public interest in participating in vaccination activities. Therefore, I also made several questions to the public, especially the Kp babakan Ds Banjarwaru to find questions that have been confused in the community. As well as how much the impact of vaccinations carried out from the beginning of 2021 to date has on the economy.